(untitled) (Philippine Journal of Agricultural Economics, 2019)
The study was conducted within ninety days duration from May 7-August 7, 2013. It aimed to determine whether the rearing system (either confinement or free – ranged) can affect the growth performance, meat quality and visceral organ characteristics of swine. Twelve (12) heads of swine used in the study which was randomly distributed into two treatments assigned in confinement and free-range systems, respectively adopting the T-test as the statistical tool. The initial weights of swine were homogenous at the start of the study. However, after obtaining the gain in weights, results revealed that swine raised in the free-range system had a higher average weight and heavier stomach compared to the confinement system. It further revealed that the back fat of the free ranged swine is thinner compared to the swine in confinement system with 1.3 cm and 2 cm, respectively. The total feed consumed by the twelve heads of experimental animals were 2,714 kilograms for 90 days period with 13.73 % return on capital for free - ranged while 5.5 % for confinement. The overall return on capital of the entire experiment was 9.6 %. Therefore, the free-range system had significantly affected the growth performance of swine.